2018
DOI: 10.1371/journal.pbio.2003446
|View full text |Cite
|
Sign up to set email alerts
|

Climate change could drive marine food web collapse through altered trophic flows and cyanobacterial proliferation

Abstract: Global warming and ocean acidification are forecast to exert significant impacts on marine ecosystems worldwide. However, most of these projections are based on ecological proxies or experiments on single species or simplified food webs. How energy fluxes are likely to change in marine food webs in response to future climates remains unclear, hampering forecasts of ecosystem functioning. Using a sophisticated mesocosm experiment, we model energy flows through a species-rich multilevel food web, with live habit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
131
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 183 publications
(146 citation statements)
references
References 79 publications
(100 reference statements)
0
131
1
3
Order By: Relevance
“…The boosting effects of CO 2 have also been observed in marine mesocosm experiments (which are more complex than laboratory experiments, but less complex than natural communities) showing the one-way flow of resources from the bottom up (Sswat et al, 2018;Ullah, Nagelkerken, Goldenberg, & Fordham, 2018). Two key ecological factors, however, influence the abundance and biomass of species: resource availability, which triggers population expansion, and consumption, which reduces the expansion to some net level (Hunter & Price, 1992).…”
Section: Discussionmentioning
confidence: 96%
“…The boosting effects of CO 2 have also been observed in marine mesocosm experiments (which are more complex than laboratory experiments, but less complex than natural communities) showing the one-way flow of resources from the bottom up (Sswat et al, 2018;Ullah, Nagelkerken, Goldenberg, & Fordham, 2018). Two key ecological factors, however, influence the abundance and biomass of species: resource availability, which triggers population expansion, and consumption, which reduces the expansion to some net level (Hunter & Price, 1992).…”
Section: Discussionmentioning
confidence: 96%
“…A meta-analysis of more than 600 experiments showed that ocean warming typically increases metabolic rates as well as primary production and consumption (Nagelkerken & Connell, 2015). Mesocosm experiments suggest that this can lead to ecosystem collapse and simplified food webs if increases in primary production are converted to unpalatable detritus and not consumed (Ullah, Nagelkerken, Goldenberg, & Fordham, 2018). These mesocosm studies, however, typically do not incorporate the effects of "species on the move" that characterise tropicalisation and which can have important effects on altered food web dynamics.…”
Section: Food Webs and Energy Fluxes In Temperate Versus Tropical Rmentioning
confidence: 99%
“…Environmental change and dispersal can both have indirect effects on communities by altering trophic interactions (Gilman et al 2010;Verreydt et al 2012), but this is an underappreciated complexity of the spatial insurance hypothesis. In both aquatic and terrestrial ecosystems, the effect of environmental change on primary producers can indirectly impact organisms at higher trophic levels (Wade et al 2017;Ullah et al 2018), and effects of environmental change on herbivores or predators can cascade down to lower trophic levels (Martin & Maron 2012;Amundrud & Srivastava 2016;Bell et al 2019). The interaction of environmental change and dispersal might entail additional indirect effects.…”
Section: Introductionmentioning
confidence: 99%